Scientific production in Latin America and the Caribbean in the period 1996-2019 - Jorge Luis León González; Alejandro Rafael Socorro Castro; Maritza Librada Cáceres Mesa; Coralia Juana Pérez Maya (Revista Cubana de Medicina Militar)
Introduction: In recent years, scientific production in Latin America and the Caribbean, as in the rest of the world, has been influenced by the development of the network of networks and the Open Access Movement. The low investment in Research, Development and innovation (R + D + i) has also affected its development; the low culture for the scientific dissemination of many researchers; and the supremacy of the English language in the most important scientific journals. Objective: To analyze the state of scientific production in Latin America and the Caribbean from 1996-2019. Development: The main theoretical constructs for bibliometric studies are analyzed. The Latin American Ranking of scientific production of journals indexed in Scopus in the period 1996-2019 is also analyzed, based on the SCImago Journal & Country Rank tool; particularly in its seven main countries. Conclusions: The results show that scientific production in Latin America and the Caribbean has had an important growth in the last 20 years; however, in increasing the socialization of scientific research results, there is concentration in only some countries and little recognition on a global scale.